Emotional intelligence and social interaction: foreign studies - Bochkova V.N.; Meshkova N.V. (Современная зарубежная психология, 2018)
The article considers the current state of the problem of emotional intelligence as one of the key competencies with increasing relevance. Approaches of foreign authors to the structure and diagnostics of emotional intelligence are presented. Particular attention is paid to the influence exerted by emotional intelligence and its components on the types of social interaction. The results of studies of its connection with prosocial and deviant behavior are analyzed. The mediators of this connection are given. Directions are offered for further study of emotional intelligence in the context of its connection with aggression and manipulation in interaction with others. Attention is drawn to the gender characteristics of emotional intelligence in behavior. Attention is paid to the development of emotional intelligence. It is concluded that when the emotional intelligence of a subject develops, its personality traits should be taken into account in order to prevent its realization in deviant and delinquent behavior